On Thorium Oxinates and Their Analytical Properties - Corsini, Alfio (My University, 1961)
2-Methyloxine is shown to be superior to oxine as a reagent for the determination of thorium. The conditions under which thorium is precipitated quantitatively and solely as 1:4 thorium 2-methyloxinate have been carefully investigated, and the results shown to lead to precise, accurate, and sensitive gravimetric, bromometric, and polaro-graphic methods for the determination of thorium. The polarography of 2-methyloxine in alkaline solution has been studied, and an attempt to elucidate the reduction process has been made. In contrast to 2-methyloxine, and in contrast to what has been believed, oxine precipitates thorium only as a compound of 1:5 stoichiometry. An accounting for this difference is made in terms of steric considerations. The structural nature of 1:5 thorium oxinate is considered, this being based on studies involving radioactive oxine and the stoichiometry of the heretofore unprepared thorium 5- and 4-methyl-oxinates.
Keywords: thorium; thorium oxinates; analytical properties